PARTISIPASI PEREMPUAN DALAM PENGELOLAAN SAMPAH RUMAH TANGGA DI RW 02 KELURAHAN NEGLASARI KECAMATAN CIBEUNYING KALER KOTA BANDUNG1 - Raden Mila Karmila (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2012)
This research aims at identifying and analyzing women's participation in domestic waste management at RW 02 Kelurahan Neglasari Cibeunying Kaler Subdistrict, Bandung City. It is a qualitative case study. The result of the research shows women participate in the domestic waste management differently along the management stages: planning, implementing, evaluating, and utilizing. The number of women who participates at the planning stage is quite high. However, the level of women's participation decreases in the following stages – implementing and evaluating.Suprisingly, in the utilizing stage, the level of women's participation mounts. Not only women but all residents at RW 02 get the benefits from the waste management activities. This can be the trigger as well as the appeal for all residents, notonly women, to get involved in such activities. Based on Arnstein's ladder of citizen participation, the women's participation at RW 02 in domestic waste management from planning to utilizing stage can be classified into the citizen control rung, in which women initiate, do, and control all the processes.